Effects of Electromagnetic Fields on Osteogenesis of Human Alveolar Bone-Derived Mesenchymal Stem Cells. (19th June 2013) - Lim, KiTaek; Hexiu, Jin; Kim, Jangho; Seonwoo, Hoon; Cho, Woo Jae; Choung, Pill-Hoon; Chung, Jong Hoon
Abstract : This study was performed to investigate the effects of extremely low frequency pulsed electromagnetic fields (ELF-PEMFs) on the proliferation and differentiation of human alveolar bone-derived mesenchymal stem cells (hABMSCs). Osteogenesis is a complex series of events involving the differentiation of mesenchymal stem cells to generate new bone. In this study, we examined not merely the effect of ELF-PEMFs on cell proliferation, alkaline phosphatase (ALP) activity, and mineralization of the extracellular matrix but vinculin, vimentin, and calmodulin (CaM) expressions in hABMSCs during osteogenic differentiation. Exposure of hABMSCs to ELF-PEMFs increased proliferation by 15% compared to untreated cells at day 5. In addition, exposure to ELF-PEMFs significantly increased ALP expression during the early stages of osteogenesis and substantially enhanced mineralization near the midpoint of osteogenesis within 2 weeks. ELF-PEMFs also increased vinculin, vimentin, and CaM expressions, compared to control. In particular, CaM indicated that ELF-PEMFs significantly altered the expression of osteogenesis-related genes. The results indicated that ELF-PEMFs could enhance early cell proliferation in hABMSCs-mediated osteogenesis and accelerate the osteogenesis.